Article RETRACTED due to manipulation by the authors How can Small Sided Game training methods (3 vs 3 and 6 vs 6) and VO2max affect basic soccer skills? - Alex Aldha Yudi; Suci Nanda Sari; Ikhwanul Arifan; Firdaus Firdaus; Mikkey Anggara Suganda; Didi Suryadi; Trisnar Adi Prabowo; Yati Yati; Sandey Tantra Paramitha; Dedi Aryadi; Ardi Nusri; Eva Faridah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Study purpose. Mastering the fundamentals of soccer is essential for skill development. Therefore, employing effective training techniques becomes crucial to enhance these fundamental soccer skills. This study aims to discern: (1) Variations in the impact of the 3 vs. 3 small-sided game method compared to the 6 vs. 6 small-sided game method on fundamental soccer skills; (2) Disparities in the impact of high and low VO2max levels on fundamental soccer skills; and (3) The repercussions of the interaction between the 3 vs. 3 small-sided game method and the 6 vs. 6 small-sided game method in conjunction with VO2max levels (high and low). Materials and Methods. A 2 x 2 factorial design was used for this experimental study methodology. 24 athletes, including 12 from the Sports Talent School (STS) West Sumatra football academy and 12 from the Indonesia Muda Soccer School, served as the research subjects. The Yo-Yo Intermittent Recovery Level 1 test is the tool used to measure VO2max. The "David Lee" competence test has been adopted as the yardstick for gauging fundamental soccer abilities. Two-way ANOVA was the method of data analysis employed, with a significance level of 0.05. Results. The study's findings are outlined as follows: (1) Indicated by a significance value of (p=0.009<0.05), there exists a disparity in the impact of training between the 3 vs. 3 small-sided game and the 6 vs. 6 small-sided game on fundamental soccer skills. With an average posttest difference of 1.69 seconds, the 3 vs. 3 small-sided game training approach proves superior to the 6 vs. 6 small-sided game method. (2) A significance value of (p=0.005<0.05) suggests a distinction in the effects of high and low VO2max levels on fundamental soccer skills. Displaying a posttest average difference of 6.23 seconds, higher VO2max levels are more advantageous than lower ones. (3) With a significance p value of 0.018<0.05, it is evident that an interaction exists among the 3 vs. 3 small-sided game, 6 vs. 6 small-sided game, and VO2max levels (high, low) concerning fundamental soccer skills. Cunclotion. based on outcomes The investigation found a strong relationship between the interaction of training techniques and VO2max on fundamental soccer playing abilities. These findings can be employed in the training of fundamental soccer game skills as a guide.